Structural performance assessment under near-source pulse-like ground motions using advanced ground motion intensity measures. - Tothong, Polsak
This paper demonstrates the effectiveness of utilizing advanced ground motion intensity measures (IMs) to evaluate the seismic performance of a structure subject to near-source ground motions. Ordinary records are, in addition, utilized to demonstrate the robustness of the advanced IM with respect to record selection and scaling. To perform nonlinear dynamic analyses (NDAs), ground motions need to be selected; as a result, choosing records that are not representative of the site hazard can alter the seismic performance of structures. The median collapse capacity (in terms of IM), for example, can be systematically dictated by including a few aggressive or benign pulse-like records into the record set used for analyses. In this paper, the elastic-based IM such as the pseudo-spectral acceleration (Sa) or a vector of Sa and epsilon has been demonstrated to be deficient to assess the structural responses subject to pulse-like motions. Using advanced IMs can be, however, more accurate in terms of probabilistic response prediction. Scaling earthquake records using advanced IMs (e.g. inelastic spectral displacement, Sdi, and IM1I&2E; the latter is for the significant higher-mode contribution structures) subject to ordinary and/or pulse-like records is efficient, sufficient, and robust relative to record selection and scaling. As a result, detailed record selection is not necessary, and records with virtually any magnitude, distance, epsilon and pulse period can be selected for NDAs.
Keywords: Near-source ground motion records; Probabilistic seismic hazard/demand analysis (PSHA/PSDA).; Structural response (drift) hazard curves; Ground motion record selection and scaling; Ground motion intensity measure (IM).; Inelastic spectral displacement (Sdi).